Participation in Development: A Case Study on Local Participation in Rural Water Supply and Sanitation in Vietnam - Toan , Dang Ngoc (Asian Journal of Agriculture and Rural Development, 2012)
Since the adoption of Doi Moi (reform) policy in 1986, local participation has attracted special attention in development projects in Vietnam. In particular, the questions of whether local participation in development projects should be promoted and whether it would be feasible became a major concern among development practitioners, as the debates on participation and project sustainability continued. While some argued that although socio-economic, cultural, ethnic and political obstacles were always present, many also believed that the promises of participation in development projects in Vietnam had been strengthened in recent times especially when the Government realised that its top-down approach in implementing development projects could only weaken local capacity. This article is an examination of how participatory approach was promoted in two villages in Daklak province, Vietnam, where a Danish-funded RWSS (Rural water supply and sanitation) project was implemented. It investigates how development was perceived differently by local people and other major stakeholders, and in turn, how participation was exercised. It also identifies the obstacles that emerged that hampered local participation and discusses how locals responded with appropriate solutions.